Effect of anti-IL-15 administration on T cell and NK cell homeostasis in rhesus macaques - DeGottardi, Maren Q. (J Immunol, 2016)
IL-15 has been implicated as a key regulator of T and NK cell homeostasis in multiple systems; however, its specific role in maintaining peripheral T and NK cell populations relative to other gamma-chain (γc) cytokines has not been fully defined in primates. Here, we address this question by determining the effect of IL-15 inhibition with a rhesusized, anti-IL-15 mAb on T and NK cell dynamics in rhesus macaques. Strikingly, anti-IL-15 treatment resulted in rapid depletion of NK cells, and both CD4(+) and CD8(+) effector memory T cells (T(EM)) in blood and tissues, with little to no effect on naïve or central memory T cells. Importantly, whereas depletion of NK cells was nearly complete and maintained as long as anti-IL-15 treatment was given, T(EM) depletion was countered by the onset of massive T(EM) proliferation, which almost completely restored circulating T(EM) numbers. Tissue T(EM), however, remained significantly reduced, and most T(EM) maintained very high turnover throughout anti-IL-15 treatment. In the presence of IL-15 inhibition, T(EM) became increasingly more sensitive to IL-7 stimulation in vivo, and transcriptional analysis of T(EM) in IL-15-inhibited monkeys revealed engagement of the JAK/STAT signaling pathway, suggesting alternative γc cytokine signaling may support T(EM) homeostasis in the absence of IL-15. Thus, IL-15 plays a major role in peripheral maintenance of NK cells and T(EM). However, whereas most NK cell populations collapse in the absence of IL-15, T(EM) can be maintained in the face of IL-15 inhibition by the activity of other homeostatic regulators, most likely IL-7.